ANALYSIS OF INCIDENCE AND MORTALITY OF GASTROINTESTINAL MALIGNANT TUMORS IN UKRAINE AND WORLDWIDE - Valeriy Zub (Acta Medica Leopoliensia)
The aim of the research is to study the epidemiological situation of malignant tumors of the gastrointestinal tract in Ukraine and worldwide.